Prevalence of coronavirus disease and its clinical manifestations in Ukraine and in the world - Vorozhbyt, B.; Sosnitskiy, A. (Actual Problems of Medicine and Pharmacy, 2021)
The article describes the clinical manifestations of coronavirus disease based on clinical studies, and also provides statistics on the disease and prevalence of coronavirus infection in Ukraine and around the world. The analysis of the research results and statistic of the disease in the world indicates that acute respiratory distress syndrome develops in severe cases.